2022
DOI: 10.3390/jmmp6050096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermo-Physical Properties of the Tool Materials on the Electro-Discharge Machining Performance of Ti-6Al-4V and SS316 Work Piece Materials

Abstract: Electro-discharge machining (EDM) is a useful non-conventional machining operation frequently applied to make different complex geometries in any conducting material. The objectives of the present paper are to study the effect of a variation of thermo-physical properties (TPP) of three different tool materials on EDM performances. The different performances compared in this paper are: material removal rate (MRR), tool-wear rate (TWR), surface roughness (SR), radial overcut (ROC), surface-crack density (SCD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Even though it still takes time and money, choosing the right cutting conditions and tools can be done through an experimental campaign [15,16]. Due to these various difficulties of conventional techniques for Ti6Al4V alloy, different non-traditional procedures were employed [17,18]. One such non-traditional process widely preferred for machining difficult-to-cut materials such as Ti6Al4V is the wire electrical discharge machining (WEDM) process.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it still takes time and money, choosing the right cutting conditions and tools can be done through an experimental campaign [15,16]. Due to these various difficulties of conventional techniques for Ti6Al4V alloy, different non-traditional procedures were employed [17,18]. One such non-traditional process widely preferred for machining difficult-to-cut materials such as Ti6Al4V is the wire electrical discharge machining (WEDM) process.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that castor oil can be used as the dielectric medium; moreover, the overcut width given by castor oil was lesser than the conventional dielectrics, but the SR achieved in the case of biodegradable dielectric was inferior to the SR magnitude realized with traditional fluids of EDM. Sethy [37] used the three distinct electrodes to determine their machining proficiency in terms of SR, MRR, OC, and EWR during EDM of titanium alloy and stainless-steel materials. Among all the used electrodes, Cu performed outstandingly for both the workpieces and gave the highest MRR, least EWR, intermediate OC, and SR. Gugulothu [38] investigated the cutting ability of deionized water and drinking water in EDM taking titanium alloy as the base material.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the numerous advantages of Ti6Al4V, their higher strength and poor thermal conductivity impose lots of challenges through conventional machining techniques such as excessive tool wear, unsuitable chip breakage, and poor surface finish [6,7]. To overcome these limitations, nonconventional machining techniques can be effectively used for machining hard materials [8][9][10]. Ti6Al4V was used in various advanced manufacturing techniques like 3D printing, including laser powder bed fusion, electron beam melting, directed energy deposition, and nonconventional machining processes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%